2019
DOI: 10.5582/bst.2019.01186
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin improves postmenopausal osteoporosis through inducing bone formation and inhibiting apoptosis in ovariectomized rats

Abstract: Postmenopausal osteoporosis (PMO) has become a public health problem worldwide. Hormonal replacement therapy (HRT) is the most popular treatment for PMO at present, but the side effects, including increased risk of endometrial cancer and breast cancer, limit its clinical use. Therefore, finding a new medication with high efficiency and less side-effects is urgently required. Dioscin is the main ingredient of some medicinal plants such as Dioscorea nipponica Makino and Dioscorea zingiberensis Wrigh. It is repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
(39 reference statements)
0
13
0
Order By: Relevance
“… 15 The best-known source of various steroidal saponins, including spirostane and furostane types, is fenugreek ( Trigonella foenum graecum ) seeds. 16 In recent years, diosgenin has attracted increasing attention due to its efficacy in treating various metabolic diseases, including diabetes, 17 CVDs, 18 neurological disease, 19 osteoporosis, 20 and hyperlipidemia, 21 in addition to anti-cancer effects, which are mediated via multiple targets and regulate various signals. 22 , 23 Numerous animal experiments and clinical trials have shown that diosgenin can reduce blood lipids by lowering plasma low-density lipoprotein (LDL) and increasing high-density lipoprotein (HDL).…”
Section: Introductionmentioning
confidence: 99%
“… 15 The best-known source of various steroidal saponins, including spirostane and furostane types, is fenugreek ( Trigonella foenum graecum ) seeds. 16 In recent years, diosgenin has attracted increasing attention due to its efficacy in treating various metabolic diseases, including diabetes, 17 CVDs, 18 neurological disease, 19 osteoporosis, 20 and hyperlipidemia, 21 in addition to anti-cancer effects, which are mediated via multiple targets and regulate various signals. 22 , 23 Numerous animal experiments and clinical trials have shown that diosgenin can reduce blood lipids by lowering plasma low-density lipoprotein (LDL) and increasing high-density lipoprotein (HDL).…”
Section: Introductionmentioning
confidence: 99%
“…MTT assay was performed as described previously 41 . Simply, Siha cells were seeded into 96-well plates at 2 × 10 3 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) stained was performed as described previously 41 . The images were subsequently acquired using a light microscope with 200× magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Bone-specific treatment is needed for treatment of osteoporosis, and individual formulations should be used in light of the benefit-risk balance (59). Some of the main ingredients in medicinal plants, such as dioscin, have proven to be effective in animal models, but more clinical trials need to be conducted (60).…”
Section: Osteoporosis Preventionmentioning
confidence: 99%